SCIENTIFIC RESEARCH METHODS FOR DEVELOPING THE GENERAL TRAINING OF YOUNG FOOTBALL PLAYERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article aims to teach the importance of general physical qualities and the methods and tools of their education, using the tools of mobile games to develop the physical qualities of young football players during the training process. A classification of action games is given for general preparation.